Seasonal Human Coronavirus Respiratory Tract Infection in Recipients of Allogeneic Hematopoietic Stem Cell Transplantation. (29th August 2020) - Piñana, Jose Luis; Xhaard, Aliénor; Tridello, Gloria; Passweg, Jakob; Kozijn, Anne; Polverelli, Nicola; Heras, Inmaculada; Perez, Ariadna; Sanz, Jaime; Berghuis, Dagmar; Vázquez, Lourdes; Suárez-Lledó, María; et al.
Abstract: Background: Little is known about characteristics of seasonal human coronaviruses (HCoVs) (NL63, 229E, OC43, and HKU1) after allogeneic stem cell transplantation (allo-HSCT). Methods: This was a collaborative Spanish and European bone marrow transplantation retrospective multicenter study, which included allo-HSCT recipients (adults and children) with upper respiratory tract disease (URTD) and/or lower respiratory tract disease (LRTD) caused by seasonal HCoV diagnosed through multiplex polymerase chain reaction assays from January 2012 to January 2019. Results: We included 402 allo-HSCT recipients who developed 449 HCoV URTD/LRTD episodes. Median age of recipients was 46 years (range, 0.3–73.8 years). HCoV episodes were diagnosed at a median of 222 days after transplantation. The most common HCoV subtype was OC43 (n = 170 [38%]). LRTD involvement occurred in 121 episodes (27%). HCoV infection frequently required hospitalization (18%), oxygen administration (13%), and intensive care unit (ICU) admission (3%). Three-month overall mortality after HCoV detection was 7% in the whole cohort and 16% in those with LRTD. We identified 3 conditions associated with higher mortality in recipients with LRTD: absolute lymphocyte count <0.1 × 10 9 /mL, corticosteroid use, and ICU admission (hazard ratios: 10.8, 4.68, and 8.22, respectively; P  < .01). Conclusions: Seasonal HCoV after allo-HSCT may involve LRTD in many instances, leading to a significant morbidity. Abstract : Seasonal human coronavirus infection in allogeneic stem cell transplant recipients was associated with considerable morbidity, in particular in those who had radiological signs of pulmonary involvement. Three-month mortality was 7% in the whole cohort and 16% in those with pulmonary involvement.